The Effect of Roundconsen (Roundtable-Concept Sentence) Learning Model on The Ability to Write Explanatory Texts for Eighth Grade Students of SMP Negeri 28 Jakarta - Rizka Shauma Alfiyanti; Fathiaty Murtadho; Nurita Bayu Kusmayati (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study aims to find out the effect of the Roundconsen (Roundtable-Concept Sentence) learning model on the ability to write explanatory texts for eighth grade students of SMP Negeri 28 Jakarta. The study was conducted in the 2019/2020 school year, the second semester in May in class VIII E. The research method used in this study was an experimental method with a pre-experimental one group. pretest-posttest design with a sample of 27 students. The prerequisite test for data analysis was performed with the Liellifors test, obtained Lo = 0.0974 <Lt = 0.1665 at the pretest with a significance level α = 0.05 and Lo = 0.0806 <Lt = 0.1665 at the posttest the significance level α = 0,05, then the data are normally distributed. Homogeneity test results obtained by fisher test, = 1,08 and = 4.23, obtained that < , this shows that the data used are homogeneous at the significance level α = 0.05. The results showed that there was an increase in the average value at the time before and after being given treatment, at the time of the pretest, the average value obtained was 47.96. Then at the posttest, the average value obtained was 83.03. Based on the results of calculating the hypothesis using the t-test, = 13.39 is greater than = 2.29 in the real level (α = 0.05). This indicates that there is an influence of the use of the roundtable concept concept on the ability to write explanatory texts in eighth grade students of SMP Negeri 28 Jakarta. This roundconsen learning model can also be used in learning to write exposition text. The use of this roundconsen model can be complemented by the use of interesting learning media. Keywords: roundconsen, roundtable, concept sentence, writing, explanatory text.